Development of a Nutrition Education Program for the Mississippi Communities for Healthy Living Nutrition Intervention Using the Diffusion of Innovations Theory - Holly F. Huye; Elaine Molaison; Laura H. Downey; Alicia S. Landry; Lashaundrea B. Crook (Journal of Human Sciences and Extension, 2017)
This research identified themes when exploring the Dietary Guidelines for Americans’ (DGA) attributes of relative advantage, compatibility, complexity, trialability, and observability to provide information for the design and structure of a nutrition education program for the Mississippi Communities of Healthy Living Nutrition Intervention. Diffusion of Innovations theory was used to develop education sessions to promote the adoption and consumption of a DGAbased healthy diet innovation in the Lower Mississippi Delta. Two focus groups were conducted with a purposive sample of 13 women in the community as well as one expert panel of six registered dietitians. Major themes identified for the DGA were Balanced Nutrition, All-inclusive, and Protective as the relative advantage; Adaptability when exploring compatibility; low complexity as Simple to Follow and Convenient and Portable; Gradual Change and Taste Tests when discussing trialability; and Modeling for observability. A Generational theme reflected participants’ desire to impart healthy behaviors to future generations. Results were used to operationalize attributes and develop 12 lesson plans.